1976
DOI: 10.1038/bjc.1976.45
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine deaminase activity in peripheral blood cells of patients with haematological malignancies

Abstract: Summary.-Adenosine deaminase (EC 3.5.4.4, ADA) has been assayed in lymphocytes, granulocytes and erythrocytes from 45 patients with haematological malignancies. Activities were uniformly low in lymphocytes from patients with chronic lymphocytic leukaemia. Variable, but abnormal activities were frequently found in multiple myeloma, untreated lymphoma and leukaemic reticuloendotheliosis. High values were observed in lymphocytes from patients with lymphoma during intensive combination chemotherapy. ADA levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
4

Year Published

1977
1977
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(25 citation statements)
references
References 8 publications
3
18
0
4
Order By: Relevance
“…ADA activity has been found to be subnormal in the lymphocytes of patients with chronic lymphocytic leukemia (9, 10, 11) a disease characterized by immunologic impairment and an abnormal proliferation of B cells (12). We previously demonstrated that the ADA activity of acute leukemia lymphoblasts is greatly increased in comparison with normal lymphocyte levels (3), and this has subsequently been confirmed by other studies (4,11). The considerable variation in absolute ADA activity among ALL patients noted previously, and the known immunological heterogeneity of ALL, prompted us to study leukemic lymphoblasts to determine whether a correlation exists between ADA activity and immunological subclasses of ALL.…”
Section: Introductionsupporting
confidence: 52%
“…ADA activity has been found to be subnormal in the lymphocytes of patients with chronic lymphocytic leukemia (9, 10, 11) a disease characterized by immunologic impairment and an abnormal proliferation of B cells (12). We previously demonstrated that the ADA activity of acute leukemia lymphoblasts is greatly increased in comparison with normal lymphocyte levels (3), and this has subsequently been confirmed by other studies (4,11). The considerable variation in absolute ADA activity among ALL patients noted previously, and the known immunological heterogeneity of ALL, prompted us to study leukemic lymphoblasts to determine whether a correlation exists between ADA activity and immunological subclasses of ALL.…”
Section: Introductionsupporting
confidence: 52%
“…However, the marked increases of ADA activity in rapidly growing hepatomas (Fig. 3) anid in acute leukaemia cells (Smyth and Harrap, 1975;Meier et al, 1976) suggest that this enzyme may correlate with the process of malignant progression. A lack of correlation of ADA activity with cell proliferation per se seems to be indicated by the unchanged values in regenerating liver and neonatal liver.…”
Section: D)1scussionmentioning
confidence: 96%
“…Decreased levels of ADA have been re-ported in lymphocytes of chronic lymphocy tic leukaemia (CLL) [12,15,18]. ADA ac tivity is markedly increased in blast cells of patients with acute lymphocytic leukaemia [12,16] and acute myelogenous leukaemia (AML) [12] but normal to moderately in creased in both leukaemias in remission as long as they were treated with cytostatic drugs [19].…”
Section: Introductionmentioning
confidence: 99%
“…ADA ac tivity is markedly increased in blast cells of patients with acute lymphocytic leukaemia [12,16] and acute myelogenous leukaemia (AML) [12] but normal to moderately in creased in both leukaemias in remission as long as they were treated with cytostatic drugs [19]. In contrast to the severe com bined immunodeficiency, increased ADA activity was found in patients treated with immunosuppressive drugs [19].…”
Section: Introductionmentioning
confidence: 99%